Sharia-Based Marketing Strategy in Increasing the Competitiveness of SMEs: A Phenomenological Study of Business Actors in North Lampung - M. Makhrus Ali; Pitri Yulianti; Betaria Susanti; Candra Saputra; Roni Susanto (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
Small and Medium-Sized Enterprises (SMEs) play a strategic role in supporting national economic growth and strengthening community-based economic resilience. However, many SMEs still face challenges in developing effective marketing strategies to enhance their competitiveness. In the context of Islamic economics, sharia-based marketing offers an alternative approach that integrates ethical, spiritual, and business values. This study aims to analyze the implementation of sharia marketing strategies and their contribution to improving SMEs competitiveness in North Lampung. The research employs a qualitative approach with a phenomenological method to explore the lived experiences of SMEs actors in applying sharia marketing principles. Data were collected through in-depth interviews, observation, and documentation involving selected SMEs entrepreneurs who have implemented Islamic business values. The findings reveal that the implementation of sharia marketing is reflected in honesty (ṣidq), trustworthiness (amanah), fairness (‘adl), transparency in transactions, and ethical digital promotion. These values strengthen consumer trust, build customer loyalty, and create value-based differentiation in the market. However, SMEs also face several challenges, including limited digital literacy, lack of sharia marketing training, and competitive market pressures. The study concludes that sharia-based marketing strategies not only function as ethical business guidelines but also serve as a sustainable competitive strategy for SMEs by integrating spiritual values, business practices, and market competitiveness.